Experimental Study on Laser Welding of AISI 304 Steel with Design of Experiments Approach. (November 2019) - Chellu, Pawan Kumar; Padmanaban, R.; Vaira Vignesh, R.; Menon, Abbhelash S; Shariff, S. M.; Padmanabham, G.
Abstract: Austenitic stainless steels find extensive applications in engineering and structural parts requiring inherent corrosion resistance. The main objective of this study is to achieve good quality butt joint in 2.5-mm thick 304 grade Stainless Steel. The joint quality is quantified in terms of weld-bead dimensions. The main issue that manufacturers face is controlling the input process parameters, to get a good quality joint, with required weld bead geometry under controlled thermal distortion. The objective of this work is to select proper input process parameters that would result in desirable weld-bead profiles with minimal heat input. The critical process parameters influencing laser-welding were found using response surface methodology technique. The results proved that the developed model could efficiently predict the responses. The criteria demonstrated a possible reduction in top width of weld bead with enhanced depth of penetration, which automatically envisaged an increase in aspect ratio. A two-factor five-level criteria design was used for predicting the optimized parameters by performing multi-response optimization. Among them, the third criterion has shown a significant decrease in heat input and it was chosen as the best-optimized parameter.